2021
DOI: 10.3390/antibiotics10020189
|View full text |Cite
|
Sign up to set email alerts
|

Veterinary Treatment Approach and Antibiotic Usage for Clinical Mastitis in Danish Dairy Herds

Abstract: Danish veterinarians’ treatment approach and use of antibiotics for clinical mastitis were investigated through a web-based questionnaire. The objective of the study was to describe and evaluate how the clinical mastitis treatment practice in Danish dairy herds corresponds to evidence from the literature and legislative requirements, in order to suggest directions for improvements and approaches encouraging the prudent use of antibiotics. In total, 174 veterinarians working with cattle received the questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 33 publications
(40 reference statements)
3
8
0
1
Order By: Relevance
“…Parenteral injections and local infusion combinations enhance antibacterial efficacy (Gruet et al., 2001), promoting quicker bacterial elimination, higher survival rates, reduced inflammation, milk loss, and culling rates (Erskine et al., 2002; Pyörälä, 2009). And 92% of Danish veterinarians prefer the combination of systemic and intramammary antibiotics for clinical mastitis (Wilm et al., 2021), which is consistent with our study's 96% combined treatment rate (Figure 2).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Parenteral injections and local infusion combinations enhance antibacterial efficacy (Gruet et al., 2001), promoting quicker bacterial elimination, higher survival rates, reduced inflammation, milk loss, and culling rates (Erskine et al., 2002; Pyörälä, 2009). And 92% of Danish veterinarians prefer the combination of systemic and intramammary antibiotics for clinical mastitis (Wilm et al., 2021), which is consistent with our study's 96% combined treatment rate (Figure 2).…”
Section: Discussionsupporting
confidence: 90%
“…of Danish veterinarians prefer the combination of systemic and intramammary antibiotics for clinical mastitis (Wilm et al, 2021), which is consistent with our study's 96% combined treatment rate (Figure 2).…”
Section: F I G U R Esupporting
confidence: 91%
See 1 more Smart Citation
“…For example, the structure of veterinary practices and types of veterinary services have been found to influence veterinary AMU (Magalhães-Sant 'Ana et al, 2017), and another study identified the need for further legal restrictions in the Netherlands to limit the influence from farmers on veterinary treatment and prescribing (Speksnijder et al, 2015a). In addition, Wilm et al (2021) identified an apparent national context-dependent preference for the route of administration when treating acute mastitis (simultaneous systemic and local treatment) among Danish veterinarians, which varied from the approaches preferred by Swedish and US veterinarians, for example (Persson Waller et al, 2016;Winder et al, 2019). Treatment approaches therefore appear to be influenced by the national context.…”
Section: Introductionmentioning
confidence: 99%
“…LysP108 was highly active under a diverse range of pH and was tolerated to different temperatures. However, its optimal working concentration was 250 µg mL -1 , which was a disadvantage relative to the small dosage of most antibiotics (Wilm et al, 2021). The antibacterial activity of LysP108 was confirmed by its ability to reduce the viability of MRSA strain XN108 (Figure 2).…”
Section: Discussionmentioning
confidence: 99%